The Mere-Reaction Effect: Even Nonpositive and Noninformative Reactions Can Reinforce Actions. Issue 3 (28th May 2015) - Hsee, Christopher K.; Yang, Yang; Ruan, Bowen
Abstract : Prior research indicates that a stimulus can reinforce an action if the stimulus is a reward (i.e., a priori positive) or carries useful information. The current research finds that if a stimulus is perceived as a reaction to an action, it can reinforce the action even if the stimulus is a priori nonpositive and noninformative. Mere reactions are reinforcing. Specifically, eight experiments, including a field experiment, demonstrate that individuals are more likely to repeat an action (e.g., inserting money in a donation box or typing a message in a textbox) if the action is followed by a stimulus (e.g., the emission of a sound or the flash of an image) than if it is not, even if the stimulus is a priori negative (e.g., an annoying sound or an aversive image) and carries no useful information. Moreover, the effect just described will occur only if the stimulus is contingent on (immediately follows) the action and perceived as a reaction to the action. Finally, by serving as a reaction, an a priori nonpositive stimulus can become positive. The present work yields theoretical implications for stimulus–response relationships and practical implications for designs of consumer products and loyalty programs.